Evaluation of individuals applying to a smoking cessation clinic at a family health center - Öztürk, Onur; Yavuz, Erdinç; Özdemir, Mikail; Ayraler, Arzu (Journal of Dependence, 2023)
Objective: This study aimed to conduct a retrospective data analysis of a smoking cessation clinic in a Family Health Center, which is rare in Turkey in terms of being defined and operating simultaneously, and to evaluate it from a primary care perspective.Method: The study was cross-sectional. The data of the smoking cessation clinic between July 2016 and September 2019 were scanned through the automation system. Demographic characteristics, addiction scores, carbon monoxide levels, number of visits, treatments, and success rates of all individuals aged 18 years and older who applied to the clinic were investigated.Results: A total of 191 individuals were interviewed 503 times. The mean age of the individuals was 39.4 ± 12.8 years, and 83.3% (n=159) were male. The one-year smoking cessation rate was 69.8%. The number of interviews increased smoking cessation. There was a weak and positive correlation between the number of interviews and carbon monoxide levels (r=0.17, p=0.02) and a weak correlation between age and carbon monoxide levels (r=0.35, p
Keywords: Family medicine; smoking cessation clinic; primary care